Sexual Pedagogies
XII, 159 p.
Keywords: Understandings of sexuality and sex education have changed dramatically, and in this collection, the authors explore the various texts that were used to teach, to entertain, to sanction and to form a sexual standard for a nation. According to Nelson and Martin, these include a puberty education, sermons on abstinence, medical writings promoting sexual fulfillment, Hollywood comedies about sexual coming of age and picture books validating homosexuality. The essays included here are designed to illustrate the many responses that Anglophone culture has had to such texts for over a century.